Unleash the power of the female brain : supercharging yours for better health, energy, mood, focus, and sex - Amen, Daniel G. (Harmony Books, 2013)
"From one of the world's leading experts on how the brain works, a step-by-step, practical program for women to achieve greater health, energy, and lasting happiness by harnessing the power of the female brain. For the first time, bestselling author and brain expert Dr. Daniel G. Amen offers insight on the unique characteristics and needs of the female brain and a practical, prescriptive program targeted specifically for women to help them thrive. In this breakthrough guide based on research from his clinical practice, Dr. Amen addresses the issues women ask about the most including fertility, pregnancy, menopause, weight, stress, anxiety, insomnia, and relationships"--